Lepto-hadronic model for the broadband emission of Cygnus X-1: preliminary results - Pepe, Carolina (2015)
Different authors have made efforts to explain the emission of the microquasar Cygnus X-1 by means of radiative models for the jet. However, so far, only leptonic models have been considered despite the fact that the presence of protons in the jet would explain some features of the high-energy emission of this source. Additionally, there is strong evidence of hadronic content in the jets of other X ray binaries. In this work we present the application of a lepto-hadronic model to the broadband electromagnetic spectrum of Cyg X-1. In such model, the injection of relativistic particles occurs in an extended region of the jet and we calculate the contribution of all particles species (including secondary particles) to the jet emissivity by several radiative process. Also, the effects of self-absortpion due to the photons created inside the jet itself are considered as well as the radiative output due to the interaction between the jet and the wind of the donor star.